On the efficiency analysis and improved design of a rubber V–belt CVT. (4th August 2014) - Lee, D.W.; Sung, C.K.
This paper presents a theoretical and experimental study on the power–loss mechanisms and efficiency of a rubber V–belt continuously variable transmission (CVT). Since the V–belt drive and CVT possessed similar motion characteristics, the power–loss mechanisms of the former were employed to explore those of the latter. Meanwhile, the distinction between them, namely speed–ratio change, was especially investigated. The power loss was divided into two parts: torque and speed losses. The effects of the design and operating parameters on loss mechanisms were analysed experimentally as the CVT operated at both steady–state and transient conditions. The experiment not only verified the results of the theoretical analysis but also revealed the trend of efficiency affected by the parameters. On the basis of this investigation, a method for improving the efficiency of the CVT was proposed. The idea was to modify the configuration of the transmission to achieve the specified speed ratio of the entire power train. The improved design was actually tested and the results showed that an increase of 10% of the efficiency was obtained.